Trends and Issues in Student-Run Peer-Reviewed Journals of Education - Tim T. Andress; Alex J. Armonda (Arizona State University, 2023)
The purpose of this mixed methods bibliometric study was to identify the trends and issues in student-run peer-reviewed journals of education and to determine predictive factors of journal longevity. To that end, a search for journals was conducted, yielding 11 journals and 1,105 records. Journals were coded for editorial procedures, goals, and guidelines. Records were coded for publication characteristics, author characteristics, and keywords and abstracts. The analysis consisted of calculating descriptive statistics for journals, authors, and affiliations, implementing text mining on titles, keywords, and abstracts, and fitting a logistic regression model to predict journal longevity. Results revealed that student-run journals are somewhat prone to gaps in publication, but that effective editorial practices such as requiring abstracts and publishing issues consistently predict journal longevity. Three themes emerged across journals: a transformative focus, leaning into the margin, and inconsistent guidelines & processes. Recommendations for student-run peer-reviewed journals of education are to (a) form sustainable editorial structures, (b) follow consistent publication patterns, (c) solicit authors purposefully, and (d) continue leaning into the margin.